Konsep Cyber Notary Dalam Pelaksanaan RUPS Melalui Media Elektronik - Sari, Riska Nova (Universitas Ekasakti, 2024)
Organizing a GMS via electronic media can be carried out as regulated in Article 77 paragraph (1) of the Limited Liability Company Law, but its implementation has only been realized since the Covid-19 pandemic. Therefore, it is necessary to carry out an in-depth study regarding the obstacles that prevent GMS via electronic media from being widely implemented since the enactment of the Limited Liability Company Law and and regarding the current development of implementing GMS via electronic media. This research aims to determine the development of the implementation of the GMS via electronic media. In this research, a normative legal research method was used using a statutory regulation approach and a conceptual approach, then analyzed using a qualitative descriptive analysis method. The results of the research concluded that the obstacles to proving that the GMS via electronic media was actually held meant that its implementation had not been carried out much since 2007. However, after the ratification of POJK Number 16 of 2020 makes it common to carry out GMS via electronic media because it has explained in more detail the procedures for its implementation compared to Article 77 of the Limited Liability Company Law.